The representation of trauma in Ian McEwan's novels "Atonement" and "Saturday" - Pitt, Daniela (My University, 2010)
ABSTRACT: Since Freud’s early work, the representation and assessment of trauma, more specifically hysteria, has given rise to numerous, albeit diverse, theories. The common factor, however, in most of these is the hypothesis that trauma in any form disrupts, at least temporarily, the growth of the individual. Through an analysis of Ian McEwan’s novels Atonement (London: Vintage Press, 2001) and Saturday (London: Vintage Press, 2006), I aim to explore how trauma within these texts is represented, viewed and engaged. In its broadest terms, trauma as explored within these texts will encompass national, historical and personal trauma. The research paper will assess the works of fiction against the background of contemporary liter-ary thematic trends which debate the manner in which trauma and anxiety are represented. Drawing on Dominic La Capra’s studies, I hope to illustrate, or even problematise, the broader concerns of trauma as represented in the texts. The choice to address La Capra will assist in the debate of tracing and assessing the form of trauma in La Capra’s theory of deny-ing, acting out or working through the trauma – in particular his notions of “absence” and “loss”. Cathy Caruth argues convincingly that trauma should be considered as a possibility of experience and I hope to draw on this assumption to show how this affects a close read-ing of the McEwan texts. My discussions will also draw on the arguments made by Maurice Blanchot’s theories on disaster detachment. Using the theories of La Capra and Blanchot as a starting point, I propose to present a close textual reading of Atonement and Saturday. I explore whether the characters in each text accommodate violent and traumatic personal episodes by reflecting on their actions and embracing a greater awareness of self and soci-ety. By positioning his protagonists in acts of trauma, McEwan provides the scope for moral growth with a view that a morally questioned existence, through self-investigation and self-determination, is a possibility of experience. My analyses will draw on the novels as exam-ples of the psyche of contemporary thought.